The role of the maternal-child nurse in promoting health among urban poor mothers - Lao-Nario, Ma. Brigette T.
Health promotion to improve the well-being of women is 1 of the concepts that is new in the Philippines. There are currently no documentation and literature on this matter. More so is the dearth of materials on the role of the nurse in implementing a program. The study is primarily aimed at identifying the role of the nurse in promoting health among urban poor women through health education. The study investigated 3 problems: 1. What are the factors affecting health promotion behavior among urban poor women? 2. Will the Maternal Child Nurse' inputs increase the health promotion behaviors of urban-poor women? 3. Are there sets of variables that positively predict health-promotion behavior? The following hypotheses were generated based on the problems stated: 1. The inputs of the maternal child nurse on health education will increase health promotion behavior. 2. There is a significant relationship between health value and health promotion behavior. 3. There is a significant relationship between locus of control and health promotion behavior. 4. There is a significant relationship between age and health promotion behavior. 5. There is a significant relationship between education and health promotion behavior. 6. There is a significant relationship between income and health promotion behavior. 7. There is a significant relationship between family size and health promotion behavior. Health promotion behavior was measured by scores of cognitive level and self-report of practices. All respondents were given pre-test/post-test interviews. The pre-test was administered individually to the respondent by appointment before the onset of the program which lasted for a period of 6 weeks. Each respondent attended 3 sessions with each session lasting for 4 hours each. The post test was given after 1 month. The following statistical tests were applied to analyze the data. 1. T-test for correlated samples to test whether the inputs of the Maternal Child Nurse will increase health promotion behavior. 2. Pearson Product Moment Correlation Coefficient to test if there is a significant relationship between health promotion behavior and health value, locus of control, age, years of education, income, family size, linear regression to identify variables that positively predict health promotion behavior. The findings are as follows: 1. The inputs of the Maternal Child Nurse increased the health promotion behavior of urban poor mothers. 2. Health value is not significantly related to cognitive level of nutrition, periodic exam, exercise and rest, and health promotive practices on exercise and rest. 3. Health locus of control is not significantly related to health promotion behavior. 4. Ages of urban poor women is not correlated with health promotion behavior. 5. There is a positive correlation between cognitive levels on exercise, periodic exam and rest. 6. Income is not correlated with health promotive behavior on nutrition, exercise, and rest. 7. No correlation was found between family size and health promotion behavior. 8. Years of education is positively predictive of cognitive levels on periodic exam, exercise and rest. 9. Income is positively predictive of cognitive level on periodic exam.